2023
DOI: 10.3390/ma16083090
|View full text |Cite
|
Sign up to set email alerts
|

Analyze the Wear Mechanism of the Longwall Shearer Haulage System

Abstract: The wear characteristics and related mechanisms of the Longwall Shearer Haulage System were investigated. Wear is one of the main reasons for failures and downtimes. This knowledge can help solve engineering problems. The research was carried out at a laboratory station and a test stand. The publication presents the results of tribological tests carried out in laboratory conditions. The aim research was to select the alloy intended for casting the toothed segments of the haulage system. The track wheel was mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…With the objective functions of the coal loading rate, cutting ratio energy consumption and cutting load, Liu et al established an optimization model for the traction speed of the shearer, providing a theoretical reference for achieving collaborative control between the cutting units and the traction units [ 11 ]. Based on friction and wear tests, Jaskowiec et al [ 12 ] analyzed the adhesive wear, three body wear and fatigue wear mechanisms of the hauling wheel and the rail, and emphasized that the wear rate in the rail bending area is 2.5 times higher than that in the straight area. Kotwica et al [ 13 ]reported a new track in the chainless traction system that mitigates hauling wheel tooth profile failure.…”
Section: Introductionmentioning
confidence: 99%
“…With the objective functions of the coal loading rate, cutting ratio energy consumption and cutting load, Liu et al established an optimization model for the traction speed of the shearer, providing a theoretical reference for achieving collaborative control between the cutting units and the traction units [ 11 ]. Based on friction and wear tests, Jaskowiec et al [ 12 ] analyzed the adhesive wear, three body wear and fatigue wear mechanisms of the hauling wheel and the rail, and emphasized that the wear rate in the rail bending area is 2.5 times higher than that in the straight area. Kotwica et al [ 13 ]reported a new track in the chainless traction system that mitigates hauling wheel tooth profile failure.…”
Section: Introductionmentioning
confidence: 99%